By His Excellency Coll. Benjamin Fletcher, captain general and governour in chief of His Majesties province of New-York, &c. A proclamation : Whereas for the ease and conveniency of the fuzileers that were in His Majesties service upon the fronteers of the province ... such persons as have credited the said fuzillers, on account of their said pay, to bring in their tickets or accounts, to the accountant general ... Given at Fort William Henry, the first day of August ... annoq ; Domini 1696 (Printed by William Bradford, printer to the Kings Excellent Majesty, 1696)
Ordering reimbursement of soldiers who have taken a post on the New York frontier.